Functional Ability, Community Reintegration and Participation Restriction among Community-Dwelling Female Stroke Survivors in Ibadan (2014)
"BACKGROUND: Stroke is not gender-discriminatory. Yet, the subject of stroke among females has apparently not received significant attention from clinical researchers. The consequences of stroke include functional and psychosocial sequelae which may cause disability, hinder community reintegration and restrict participation. The inter-relationships among functional ability, community reintegration and participation restriction of community-dwelling, female stroke survivors in Ibadan were assessed in this descriptive study. METHODS: Fifty-two community-dwelling female stroke survivors (mean age = 56.55±9.91 years) were surveyed using consecutive sampling technique. Their functional ability level was measured using the Functional Independence Measure (FIM) while London Handicap Scale (LHS) was used to assess their participation restriction. Data were analyzed using Spearman Rank Correlation Coefficient (rho) and Mann-Whitney U test at p = 0.05. RESULTS: Significantly positive correlations (p< 0.05) were found between functional ability and community reintegration (r = 0.54; p = 0.01) as well as between participation restriction and community reintegration (r = 0.34; p = 0.05). Individuals with left hemiplegia had significantly higher mean rank scores in functional ability (30.41) than those who had right hemiplegia (mean rank scores = 21.94). CONCLUSION: Functional ability which appears to be related to stroke laterality showed positive association with both community reintegration and participation restriction. This suggests that improving the functional ability of the stroke survivors may reduce participation restriction and enhance their reintegration into the community. A similar study which compares male and female stroke survivors in the same community is thus necessary. "